1996
DOI: 10.1128/jcm.34.11.2748-2755.1996
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Babesia bovis infections in cattle by using PCR-based tests

Abstract: The sensitivity and specificity of PCR tests based on the small-subunit rRNA gene sequence of Babesia bovis were compared in a blind study of experimentally infected cattle with the corresponding parameters of the complement fixation (CF) test currently used in the United States to screen for bovine babesiosis. Cattle were experimentally infected with a single inoculum of a cloned laboratory strain of B. bovis. Blood samples were collected and tested over a period covering from the day of infection to 10 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(40 citation statements)
references
References 27 publications
3
37
0
Order By: Relevance
“…Furthermore, in experimental animals, T. annulata could be detected simultaneously with T. mutans, T. orientalis, B. divergens, B. bovis, and B. bigemina. After Imidocarb treatment the B. bovis signal was completely lost, confirming the earlier findings of Calder et al (6). Our B. bigemina results are similar to those obtained with the previously published B. bigemina-specific PCR (15).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, in experimental animals, T. annulata could be detected simultaneously with T. mutans, T. orientalis, B. divergens, B. bovis, and B. bigemina. After Imidocarb treatment the B. bovis signal was completely lost, confirming the earlier findings of Calder et al (6). Our B. bigemina results are similar to those obtained with the previously published B. bigemina-specific PCR (15).…”
Section: Discussionsupporting
confidence: 93%
“…The detection limit of the T. annulata PCR based on the Tams1 gene (13) was 4.8 ϫ 10 Ϫ5 %, which is highly comparable with the sensitivity found for the RLB. For B. bovis, a detection of 10 Ϫ7 to 10 Ϫ8 % parasitemia was achieved by using 18S PCR and a specific probe followed by very sensitive phosphorimager detection (6). These investigators demonstrated that B. bovis parasitemia fluctuates and sometimes even escapes detection by their assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of generated bands is indicated. (Calder et al, 1996;Gubbels et al, 1999). The newly presented nPCR assays may thus significantly reduce or eliminate false negative test results as compared to previously reported assays.…”
Section: Molecular and Serological Detection Of B Bovis And B Bigemmentioning
confidence: 91%
“…In contrast, PCR-based diagnostics has the potential to detect directly the parasite with high specificity and sensitivity (Mosqueda et al, 2007(Mosqueda et al, , 2012. Notwithstanding, it has been demonstrated that parasites of carrier animals often escape detection even from highly sensitive PCR-based diagnostic methods, posing a challenge to further optimize nPCR assay design and format in order to maximize sensitivity (Calder et al, 1996;Gubbels et al, 1999;Oliveira-Sequeira et al, 2005;Martins et al, 2008).…”
Section: Introductionmentioning
confidence: 99%